On the Role of ROS and Glutathione in the Mode of Action Underlying Nrf2 Activation by the Hydroxyanthraquinone Purpurin - Qiuhui Ren; Wouter Bakker; Sebastiaan Wesseling; Hans Bouwmeester; Ivonne M. C. M. Rietjens (MDPI AG, 2023)
Purpurin is a major anthraquinone present in the roots of Rubia cordifolia (madder). Purpurin is known to activate Nrf2 (Nuclear transcription factor erythroid 2-related factor 2) EpRE (electrophile responsive element) mediated gene expression as a potential beneficial effect. This study aimed to elucidate the balance between the electrophilicity or pro-oxidant activity of purpurin underlying the Nrf2 induction. For this, Nrf2 activation with modified intracellular glutathione (GSH) levels was measured in an Nrf2 CALUX reporter gene assay. In addition, both cell-free and intracellular ROS formation of purpurin with modified (intracellular) GSH levels at different pH were quantified using the DCF-DA assay. GSH adduct formation was evaluated by UPLC and LC-TOF-MS analysis. GSH and GSSG levels following purpurin incubations were quantified by LC-MS/MS. We show that Nrf2 induction by purpurin was significantly increased in cells with buthionine sulfoximine depleted GSH levels, while Nrf2 induction was decreased upon incubation of the cells with N-acetylcysteine being a precursor of GSH. In cell-free incubations, ROS formation increased with increasing pH pointing at a role for the deprotonated form of purpurin. Upon incubations of purpurin with GSH at physiological pH, GSH adduct formation appeared negligible (<1.5% of the added purpurin). The addition of GSH resulted in conversion of GSH to GSSG and significantly reduced the ROS formation. Together these results demonstrate that Nrf2 induction by purpurin originates from intracellular ROS formation and not from its electrophilicity, which becomes especially relevant when intracellular GSH levels can no longer scavenge the ROS. The present study demonstrated that the efficiency of intracellular Nrf2 activation by purpurin and related anthraquinones will depend on (i) their pKa and level of deprotonation at the intracellular pH, (ii) the oxidation potential of their deprotonated form and (iii) the intracellular GSH levels. Thus, the Nrf2 induction by purpurin depends on its pro-oxidant activity and not on its electrophilicity.